2016
DOI: 10.1007/s00330-016-4462-8
|View full text |Cite
|
Sign up to set email alerts
|

Added value of diffusion-weighted magnetic resonance imaging for the detection of pancreatic fluid collection infection

Abstract: • DW improves MR diagnostic accuracy to detect infection of PFC • Infected PFCs show lower ADC compared to non-infected ones (P < .031) • DW-MR images are easy to interpret especially for non-experienced radiologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Areas of pancreatic necrosis do not show contrast enhancement. Some authors have suggested that the presence of superadded infection in acute pancreatic or peripancreatic collection may show diffusion restriction 37 ; however, this is not universally accepted, and infection is often proven by aspiration.…”
Section: Pancreatic Inflammationmentioning
confidence: 99%
“…Areas of pancreatic necrosis do not show contrast enhancement. Some authors have suggested that the presence of superadded infection in acute pancreatic or peripancreatic collection may show diffusion restriction 37 ; however, this is not universally accepted, and infection is often proven by aspiration.…”
Section: Pancreatic Inflammationmentioning
confidence: 99%
“…The CT scan can determine the extent of area involved by the necrosis and can give precise details about the exact site, amount, possible communication and structures in the proximity. High resolution contrast enhancement MRI through its ability to define the composition of the necrotic collection (liquid content, necrotic sediment, clotted blood, big size debris) is useful to select the best technique for the drainage, and hence, increases the chances of effective drainage[104]. The MRI is 67% sensitive and 97% specific in detecting the presence of a superimposed infection in the pancreatic fluid collections, which gives a weaker diffusion coefficient ( P = 0.031).…”
Section: Managementmentioning
confidence: 99%
“…35 Finally, DWI can also be useful in the evaluation of pancreatic/peripancreatic collections, as lower ADC values (as a result of cellular debris) can be indicative of superadded infection. 31,36 Quantification of T 2 signal using T 2 mapping (Supplementary Material 1) in acute pancreatitis has not been reported to date, but typically increased pancreatic/peripancreatic T 2 signal ( Figure 2) has the potential to yield useful quantitative markers.…”
Section: Quantitative Pancreatic Mrimentioning
confidence: 99%